FORENSIC SCIENCE MODERNISATION IN NEW CRIMINAL LAWS: CAPACITY, QUALITY ASSURANCE, AND ADMISSIBILITY CHALLENGES - Marripalli Vishwanath Vasudevudu (IJRDO - Journal of Social Science and Humanities Research, 2026)
The purpose of this study is to explore the changing nature of forensic sciences that now exist under the New Criminal Law 2020, i.e. under Bharatiya Nyaya Sanhita & Bharatiya Nagarik Suraksha Sanhita within India. In particular, this study focuses on the three main aspects of forensic science's place in the above legislations, i.e. the capacity, quality assurance, and admissibility. Through this analysis, the author argues that while this change in the statutes of Indian criminal law is an attempt to institutionalise an evidence-based approach to the investigation of crime as well as to strengthen the scientific discipline of criminal justice, the new criminal laws have not resolved several root causes of the systemic challenges as outlined in this research. Specifically, a weak forensic infrastructure, a lack of suitably trained forensic professionals, and lengthy case backlogs impede the timely analysis of evidence. Furthermore, there are numerous inconsistencies regarding quality assurance. There exists a lack of standardisation in accreditation, no uniform practices for conducting forensic analyses, and contamination issues that create uncertainty regarding the reliability of forensic results. Finally, there continue to be challenges associated with the admissibility of forensic results. Judges are continuing to scrutinise forensic evidence by assessing issues regarding the chain of custody, the validity of the analytical method used, and adherence to legal requirements. Without addressing the interdependencies of these challenges, there is a high possibility that the full transformative potential of forensic science to deliver justice to the people of India is unlikely to occur.